Mobile Remote Control for Home Automation - Miramontes Meza, Ramses; Escamilla del Río, Laura Victoria; Aquino Santos, Raúl Teodoro (International Journal of Interactive Mobile Technologies (iJIM), 2013)
Existing home automation technologies permit persons to control elements of the home using a computer connected to a local network. However, the real challenge is to remotely control objects, permitting users to exercise greater freedom and versatility. This work presents an inexpensive controller device developed for high density constructions typical of many developing countries throughout the world that is designed to remotely control home luminescence, air conditioner and water pumps through mobile devices such as a smart phone or tablet. Results show the packet delivery was acceptable within a range of 15 meters in a concrete, two-story dwelling, thus demonstrating its applicability in small homes in countries which share the same construction features as those of Mexico.